Biological Characteristics and Antimicrobial Activity of Endophytic Streptomyces sp. TQR12-4 Isolated from Elite Citrus nobilis Cultivar Ham Yen of Vietnam - Phan Thi Hong-Thao; Nguyen Vu Mai-Linh; Nguyen Thi Hong-Lien; Nguyen Van Hieu (International Journal of Microbiology)
Ham Yen orange (Citrus nobilis Lour) is the highly valuable commercial fruit of Vietnam. With the blooming of fruit production and farming area, this specialty crop is facing threats from several serious diseases; therefore the search for new effective biocontrollers is required to prevent the existing excessive use of fertilizers and plant protection chemicals. Endophytic actinomycetes are of great scientific interest due to their high potential of application in agriculture and pharmaceutical research. In this work, endophytic actinomycetes were isolated from a native orange species of Northeast mountainous province Tuyen Quang. Among 49 isolates obtained, the isolate TQR12-4 strongly inhibited test pathogens Colletotrichum truncatum, Geotrichum candidum, Fusarium oxysporum, and F. udum. This isolate gave comparatively high biomass yields on different substrates, for example, carboxy methyl cellulose, starch, protein, and chitin, within a wide range of temperature from 15 to 45°C and pH from 4 to 10. Sequence analysis of 16S rDNA gene showed that TQR12-4 shared 99% similarity to Streptomyces prasinopilosus; however, it slightly differed from the latter in spore morphology and hence was named as Streptomyces sp. TQR12-4. A thermostable antifungal substance of nonpeptide nature produced by Streptomyces sp. TQR12-4 had MIC against Fusarium udum of 100 μg/mL and 400 μg/mL respective to extract fractions X4 and X5.